2011
DOI: 10.5152/akd.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of the vertical vein left intact during the surgery for total anomalous venous connection and its effects on ventricular functions

Abstract: Total anormal pulmoner venöz bağlantı nedeniyle yapılan ameliyatta açık bırakılan vertikal venin akıbeti ve ventrikül fonksiyonlarına etkisi 2011; 11: 638-42) Original Investigation Özgün Araşt›rma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Of those patients, 15% to 60% ultimately had to undergo VV ligation because of large shunts. 15 As described in a few case reports, transcatheter approach may be successful at centers with ACHD expertise. However, most of these reports have minimal follow-up, and therefore, the durability of this solution remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Of those patients, 15% to 60% ultimately had to undergo VV ligation because of large shunts. 15 As described in a few case reports, transcatheter approach may be successful at centers with ACHD expertise. However, most of these reports have minimal follow-up, and therefore, the durability of this solution remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…13 Saritaş et al showed that unligated vertical vein provides relief in the pressure of suprasystemic pulmonary artery. 14 The important issues in deciding to close of the vertical vein after surgery are the amount of shunt, the direction of shunt, and pulmonary vascular resistance. The advantages of Amplatzer Vascular Plug devices are allowing total closure of vertical vein, low embolisation rate, easing of retrieval when device has been embolised, easily repositioning until releasing of device.…”
Section: Discussionmentioning
confidence: 99%